Case of prolonged presence of foreign magnetic bodies in the gastrointestinal tract of a child - A.V. Hlutkin; A.V. Khmelenko; V.V. Khartanovich; D.S. Krivetsky (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Foreign bodies of the digestive canal in children are often found in preschool age. Special attention should be paid to such aggressive foreign bodies as neodymium magnets. The authors describe a clinical case of prolonged presence of magnetic foreign bodies in the gastrointestinal tract of a child. The clinical picture, diagnosis and combined treatment of a child with foreign bodies are presented. It is confirmed that the waiting tactic of dynamic observation of the passage of several magnetic balls through the gastrointestinal tract can lead to the development of complications that can be accompanied without clinical manifestations. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of an participating institution.The informed consent of the child's parents was obtained from the studies.